Osmanlı devleti'nde ceza yargılaması - Akman, Mehmet (İstanbul : Eren, 2004)
Islamic law; Turkey; history.
Osmanli devleti'nde ceza yargilamasi / Mehmet Akman.
Bibliografija: str. [185]-193
Indeks
Keywords: Criminal justice, Administration of -- Turkey -- History; Criminal justice, Administration of -- Turkey -- History -- Sources -- Bibliography; Osmansko Carstvo -- kazneno pravosuđe -- administracija -- bibliografija